Prevalence and Antimicrobial Susceptibility Pattern of Pseudomonas aeruginosa Isolated from Various Clinical Samples in a Tertiary Care Hospital - Mahaseth, Surya Narayan; Chaurasia, Lokeshwar; Jha, Brajesh; Sanjana, Raj Kumari (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Pseudomonas aeruginosa is one of the leading causes of hospital acquired infections. Increased resistance in this organism continues to pose a significant threat to patient care because of limited therapeutic options. The main objective of this study was to find out the prevalence and current antimicrobial susceptibility pattern of P. aeruginosa isolates obtained from various clinical samples at a tertiary care hospital. Material and Methods: The study was conducted in a tertiary care hospital in Bharatpur, Chitwan, Nepal on 453 isolates of Pseudomonas aeruginosa from various clinical samples. The colonies which were grown on culture media were identified by different standard biochemical tests. Antimicrobial susceptibility testing was done using Kirby–Bauer disc diffusion method and the results were interpreted according to the CLSI guidelines. Quality control of the test was done by standards ATCC strain of P. aeruginosa 27853. Results: This present study revealed the prevalence rate of P. aeruginosa was 11.29%. Piperacillintazobactam was the most sensitive chemotherapeutic agent with 94.26% susceptibility rate, followed by imipenem 89.40% and levofloxacin 88.08%. Amikacin showed better susceptibility rate 67.33% than that of gentamicin 48.78%; the susceptibility rate to cephalosporin and aztreonam was relative very low. Most of the P. aeruginosa strains were isolated from clinical samples like sputum 206, urine 81, respiratory secretion 76, and pus 35. Out of 453 clinical isolates, 167(36.86%) clinical isolates of P. aeruginosa were found to be MDR. Conclusion: Most of the P. aeruginosa strains were isolates from sputum, urine, respiratory secretions and pus samples and were found to be MDR. Piperacillin-tazobactam was the most sensitive chemotherapeutic agent followed by Imipenem, levofloxacin.